Beyond preemption : force and legitimacy in a changing world - Daalder, Ivo H. (Book collections on Project MUSE., 2007)
"Makes proposals for how to forge a new international consensus on the use of force, including its preemptive use, to address today's interrelated threats of terrorism, weapons of mass destruction, and humanitarian crises. Considers how these strategies could be best legitimized and made palatable to domestic and international communities"--Provided by publisher